The unequal(?) burden of unemployment in Sweden during the first wave of the COVID-19 pandemic - Marcus Eliason (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
The first wave of the COVID-19 pandemic and the measures enforced to combat it have led to a decline in economic activity unprecedented since the Great Depression. Worldwide, millions, and yet millions, of people have lost their jobs-either temporarily or permanently. At first, the COVID- 19 pandemic was characterised as a leveller, but since then it has become increasingly clear that it is nothing of the sort. Using aggregated data on jobseekers registered with the Swedish Public Employment Service I document how the inflow, outflow, and stock of jobseekers evolved for various demographic groups during the first wave of the pandemic. Similar to previous studies, I find that already disadvantaged groups, such as the younger and to some extent also the foreign born were more adversely affected during the first wave of the COVID-19 pandemic. However, that is not to say that other groups were not affected, and contrary to many of these same studies I do not find that women were disproportionally affected.
Keywords: I12; I18; J63; J64; 330; COVID-19; unemployment; jobseekers